ANALYSIS OF FACTORS AFFECTING THE VOLUME OF COTTON IMPORTS IN INDONESIA - Anggita Farah Adiba; Sishadiyati (Media Ekonomi, 2025)
The textile and textile product industry is a strategic sector in Indonesia that is highly dependent on cotton imports, most of its cotton fibre requirements sourced from international markets. This dependence arises from limited domestic cotton production, primarily due to land-use conversion for more profitable crops, pest infestations, and unfavourable climatic conditions for cotton cultivation. This study aims to investigate the effects of domestic cotton production, international cotton prices, and textile exports on cotton imports in Indonesia during the period 2009 to 2023. This study employs a quantitative approach to analyze the factors influencing cotton imports in Indonesia, utilizing time series data covering the period from 2009 to 2023, with cotton import volume (tons) specified as the dependent variable, while domestic cotton production (tons), international cotton prices (USD/ton), and textile exports (tons) were included as independent variables. The empirical findings demonstrate that domestic cotton production has a positive and statistically significant impact on the volume of cotton imports. Similarly, textile exports exert a positive and significant influence on cotton import volumes. In contrast, international cotton prices do not have a significant effect. This is due to the low level of domestic cotton production, which is insufficient to meet the demands in Indonesia. The limited domestic supply forces the industry to rely heavily on imports, regardless of fluctuations in international cotton prices.